2018
DOI: 10.1016/j.appet.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Oral processing behaviours that promote children's energy intake are associated with parent-reported appetitive traits: Results from the GUSTO cohort

Abstract: Oral processing behaviours associated with faster eating rates have been consistently linked to increased energy intakes, but little is known about their links to children's appetitive traits. This study used the Child Eating Behaviour Questionnaire (CEBQ) to explore cross-sectional and prospective associations between parent-reported appetitive traits and observed oral processing behaviours. Participants were 195 children from the Growing Up in Singapore Towards healthy Outcomes cohort, who participated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Additionally, slowness in eating was the only food avoidance subscale that was significantly associated with lower BMI z-scores at all time points studied in children aged 3 (Quah et al, 2017), 5 and 6 years in our cohort, and the direction of association concurs with previously reported studies (Sleddens et al, 2008; Viana et al, 2008; Webber et al, 2009; Santos et al, 2011). In a separate study within our cohort, we have also shown that the reported slowness in eating scores at ages 5 and 6 captured using the CEBQ had significant negative correlations with measured eating rates (grams/minute) at similar time points (Fogel et al, 2017). This implies that the parental perception of the child’s slowness in eating concurs with actual eating rates measured in the laboratory, at least in terms of identifying slower eaters.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, slowness in eating was the only food avoidance subscale that was significantly associated with lower BMI z-scores at all time points studied in children aged 3 (Quah et al, 2017), 5 and 6 years in our cohort, and the direction of association concurs with previously reported studies (Sleddens et al, 2008; Viana et al, 2008; Webber et al, 2009; Santos et al, 2011). In a separate study within our cohort, we have also shown that the reported slowness in eating scores at ages 5 and 6 captured using the CEBQ had significant negative correlations with measured eating rates (grams/minute) at similar time points (Fogel et al, 2017). This implies that the parental perception of the child’s slowness in eating concurs with actual eating rates measured in the laboratory, at least in terms of identifying slower eaters.…”
Section: Discussionmentioning
confidence: 53%
“…We recently reported that faster self-reported eating rates (SRER) were associated with a significantly higher energy intake, body weight, body mass index (BMI) and adiposity in a population-based cohort [3]. Differences in eating rates are believed to have a heritable component [4], and the emergence of a faster, 'obesogenic' eating style [5] has been shown to be associated with higher fat-free mass, basal metabolic rate and energy requirements [6], and with more rapid weight gain, stronger food approach appetitive traits [7,8] and poorer inhibitory control [9] among children.…”
Section: Introductionmentioning
confidence: 99%
“…When children were eating at faster rates, parents were not necessarily instructing them to slow down, which raises the question of which behaviour(s) parents are responding to when using instructions focused specifically on eating speed. Though the exact eating behaviour cues that signal a child's eating rate to a parent are not well understood, recent evidence suggests that parents probably take into consideration both the speed and duration of eating when defining the child as a slow eater (Fogel et al, ). This is also supported by the results of the current study, as parents were more frequently using the instructions to slow down when children were eating faster and for a longer duration, suggesting that parents perceived this eating style as the most problematic.…”
Section: Discussionmentioning
confidence: 99%